Analysis of The Influence of Product Quality, Price, and Location on Consumer's Decision To Buy Peanuts at UD. Berkah Alam - Nurhuda, Alfian; Muslih, Basthoumi; Soeprayitno, Edy Djoko (Proceeding Kilisuci International Conference on Economic & Business, 2023)
Research Objectives: The purpose of this study was to analyze whether there is a significant influence between the variables of product quality, price, and location simultaneously or partially on purchasing decisions at UD. Berkah Alam. Research Method: The approach used in this study is a quantitative approach and the type of causal research, the sampling technique uses multivariate analysis, the sample size used is 40 consumers, and the data analysis technique uses descriptive statistics, classical assumption test, multiple linear regression, coefficient of determination, and test hypothesis with SPSSv25 tools. Research Finding: The results showed that product quality, price, and location had a significant effect both partially and simultaneously on purchasing decisions at UD. Berkah Alam.